The Influence of Shallot Price Fluctuations on the Improvement of Farmers' Welfare in Pekalobean Village, Anggeraja District, Enrekang Regency - Hermawaty Remba Kasim; Citra Ella Atmisari; Mochtar Lutfi (PINISI Discretion Review, 2019)
The purpose of this study was to determine the Effect of Shallot Price Fluctuations on Farmers' Welfare Improvement in Pekalobean Village, Anggeraja District, Enrekang Regency. This type of research is quantitative with a simple linear regression analysis. The research data were obtained from the results of distributing questionnaires to shallot farmers in Pekalobean Village, Anggeraja District, Enrekang Regency, as many as 50 respondents. The results of this study indicate that the fluctuations in the price of shallots affect the welfare of farmers in Pekalobean Village Anggeraja District Enrekang Regency by 12% with a tcount of 2.520 greater than the table of 2.010 with a significance of 0.015 less than 0.05.